EVALUATION OF THE PHYSICAL CONSTRUCTION BUDGET FOR THE DEVELOPMENT OF STATE JUNIOR HIGH SCHOOL (SMPN) 14 IN BANDUNG - Jujuk Kusumawati; Djoko Subagijo; Udien Yulianto; Yudi Setiawan (LPPM YPITI, 2026)
This study aims to evaluate the accuracy of the physical budget ceiling for the construction of SMP Negeri 14 Bandung at the conceptual stage using a conceptual cost estimation approach and identify parameters that influence the level of cost estimation accuracy using the Relative Importance Index (RII) method. Cost estimates were calculated using a parametric method, with data tabulation based on parameters in PUPR Ministerial Regulation No. 22/PRT/M/2018. A multicriteria assessment was conducted by referring to previous studies regarding the accuracy limits of cost estimates. Analysis was conducted using validity, reliability, correlation, and RII calculations to identify the parameters most influential on cost estimation accuracy. The results showed that the conceptual cost estimate was Rp 8,415,480,000.00, while the physical budget ceiling was set at Rp 7,410,370,000.00. There was a difference of Rp 1,005,110,000.00 (-11.94%), indicating that the budget ceiling was lower than the estimate, thus being assessed as